2022
DOI: 10.1039/d2se00873d
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO2-to-CO photoreduction over an orthophosphate semiconductor via the direct Z-scheme heterojunction of Ag3PO4 quantum dots decorated on SnS2 nanosheets

Abstract: Direct Z-scheme heterojunctions are widely used for photocatalytic water splitting and CO2 reduction by facilitating well-separated photogenerated charge carriers and spatial isolation of redox reactions. Here, using a facile two-step...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…On the other hand, it was found that developing a Z-scheme heterostructure by Ag 3 PO 4 , despite some benefits, caused decreasing SVs in Ag 3 PO 4 /SnO 2 . 122…”
Section: Application Of Epr In Energy Conversion Catalysismentioning
confidence: 99%
“…On the other hand, it was found that developing a Z-scheme heterostructure by Ag 3 PO 4 , despite some benefits, caused decreasing SVs in Ag 3 PO 4 /SnO 2 . 122…”
Section: Application Of Epr In Energy Conversion Catalysismentioning
confidence: 99%